Comorbidities and complications in adults with pyruvate kinase deficiency. (24th January 2021) - Boscoe, Audra N.; Yan, Yan; Hedgeman, Elizabeth; van Beers, Eduard J.; Al‐Samkari, Hanny; Barcellini, Wilma; Eber, Stefan W.; Glader, Bertil; Yaish, Hassan M.; Chonat, Satheesh; Sharma, Mukta; Kuo, Kevin H. M.; et al.
Abstract: Objectives: Pyruvate kinase (PK) deficiency is caused by PKLR gene mutations, leading to defective red blood cell glycolysis and hemolytic anemia. Rates of comorbidities and complications by transfusion history and relative to the general population remain poorly quantified. Methods: Data for patients aged ≥ 18 years with two confirmed PKLR mutations were obtained from the PK deficiency Natural History Study (NCT02053480). Frequencies of select conditions were compared with an age‐ and sex‐matched cohort from a general insured US population without PK deficiency. Results: Compared with the matched population (n = 1220), patients with PK deficiency (n = 122) had significantly higher lifetime rates of osteoporosis, liver cirrhosis, and pulmonary hypertension; splenectomy and cholecystectomy rates were also significantly higher in the 8 years before the index date. Sixty‐five (53.3%) patients with PK deficiency were classified as regularly transfused, 30 (24.6%) as occasionally transfused, and 27 (22.1%) as never transfused. Regularly transfused patients were significantly more likely than never transfused patients to have had splenectomy, cholecystectomy, and/or thrombosis. Liver iron overload was reported in 62% of patients and occurred regardless of transfusion cohort. Conclusions: Even never transfused patients with PK deficiency had higher rates of select comorbidities and complications than individuals without PK deficiency.